2019
DOI: 10.1155/2019/2626374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia on Gene Expression in Cell Populations Involved in Wound Healing

Abstract: Wound healing is a complex process regulated by multiple signals and consisting of several phases known as haemostasis, inflammation, proliferation, and remodelling. Keratinocytes, endothelial cells, macrophages, and fibroblasts are the major cell populations involved in wound healing process. Hypoxia plays a critical role in this process since cells sense and respond to hypoxic conditions by changing gene expression. This study assessed the in vitro expression of 77 genes involved in angiogenesis, metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 115 publications
(118 reference statements)
0
21
0
1
Order By: Relevance
“…The C t cut-off was set to 35. Expression data were normalized to the housekeeping gene RPLP0 (ribosomal protein lateral stalk subunit P0) and elaborated using the ∆∆C t method based on Pfaffl equation [62].…”
Section: Qpcrmentioning
confidence: 99%
“…The C t cut-off was set to 35. Expression data were normalized to the housekeeping gene RPLP0 (ribosomal protein lateral stalk subunit P0) and elaborated using the ∆∆C t method based on Pfaffl equation [62].…”
Section: Qpcrmentioning
confidence: 99%
“…Many CAs are detected in normal skin [5][6][7], and we showed earlier that the expression of Car4 and Car9 mRNAs are elevated in murine skin wounds compared to normal skin during the hypoxic phase of wound healing [8]. This is thought to be associated with the lack of oxygen in the wound milieu [8,9]. Furthermore, topically administered recombinant CA IV accelerates wound closure [8].…”
Section: Introductionmentioning
confidence: 93%
“…study showed that the occlusive environment created by the interactive dressing not only decreases the risk of bacterial infection but also provides a moist environment that increases regeneration. [ 37 ]…”
Section: Evolutionary Trend Of Wound Dressingsmentioning
confidence: 99%